Schitt$ Creek. Season 5 [videorecording (DVD)] - Levy, Eugene, 1946-; Levy, Daniel, 1983- (Lions Gate Entertainment Inc., 2020)
The Roses' personal investment in the town of Schitt's Creek rises as Johnny's partnership in the hotel lands him and Stevie at the Hospitality Awards, Moira returns from filming a horror movie in Bosnia to direct the community-theatre musical, and David plans a surprise birthday party for Patrick which also ends up surprising his parents. The opening night of "Cabaret" with both Stevie and Patrick as reluctant leads, almost overshadows the big announcement David needs to make.